Self-versus Proxy-Reported Pain in Children with Cerebral Palsy: A Population-Based Registry Study of 3783 Children - Gunnar Hägglund; Amanda Burman-Rimstedt; Tomasz Czuba; Ann I. Alriksson-Schmidt (SAGE Publishing, 2020)
Objective: To assess how the prevalence of pain in a population-based sample of children and adolescents with cerebral palsy (CP) differ based on self- or proxy reporting. Methods: This cross-sectional registry study included 3783 children (58% boys), 1 to 18 years old, enrolled in the Swedish follow-up program for CP. Logistic regression was used to regress source of reporting (self or proxy) on the presence of general pain adjusted for age, sex, Gross Motor Function Classification System (GMFCS), and Communication Function Classification System (CFCS) levels, including marginal effects between source of reporting and adjusted covariates. Results: The pain item was self-reported in 45%, proxy-reported in 51%, and information was missing in 3%. Pain was reported in 44% of those who self-reported and in 41% of those who proxy-reported ( P = .04). The logistic regression showed that the average marginal effects of proxy versus self-reported pain were lower among children at GMFCS level IV (−0.14, 95% CI −0.17 to −0.03) and CFCS level I (−0.09, CI −0.16 to −0.01) and higher at CFCS level III (0.11, CI 0.00-0.22). There were no statistically significant differences in average marginal effects related to age, sex, or the other GMFCS and CFCS levels between proxy and self-reporting. Conclusions: Pain was more often reported by those who self-reported. However, after adjusting for age, sex, CFCS level, and GMFCS level, the proportion of reported pain was almost equal between self and proxy-reporting. Assuming that the self- and proxy-reported groups were not significantly different on relevant factors not controlled for the results indicate that presence of pain is equally reported by children and parents.